The Use of Question Cube as a Learning Media in English Skills Teaching: A Literature Review - Nasrullah, Nasrullah; Sari, Normalya; Amelia, Rizky (English Department, Universitas Negeri Surabaya, 2023)
Reading is an important skill in learning English but sometimes students have some problems with the reading process because of their limited vocabulary knowledge, poor comprehension, and difficulty to recall information after reading. The teachers need to help the students to resolve these problems by creating learning media in teaching reading. Based on previous research, some researchers used story cubes and dice games as learning media by using the cube in pictures and cube in the shape of dice to improve various skills such as grammar, vocabulary, and writing skills, but there are no researchers discussed Question Cube by using questions in the cube as a learning media in teaching reading comprehension. Therefore, in this research, the researcher offered an alternative media which is a question cube media to teach students. The purpose of this research is to find out whether or not Question Cube is an effective medium to increase students' reading comprehension. In this research, the researcher used a literature review research method by collecting 30 articles taken from Google Scholar and ResearchGate. These articles were then sorted and analyzed to obtain data. From 30 articles that researchers have read, it showed that Question Cube media can bear positive change and improvement toward students' reading comprehension. In addition, it also played a considerable role in teaching vocabulary, boosting writing skills, and improving the learners’ grammar as well as other several benefits in EFL instructional process